Contribution of Narcissistic Tendencies and Social Rejection to Aggressive Behavior of Male Students - Lusi Ramadhani; Dina Sukma (Postgraduate, University of Mataram, 2024)
Aggressive behavior in adolescents, especially in male students, is often influenced by two significant factors: narcisstic and social rejection. This study aims to analyze the contribution of narcissistic tendencies and social rejection experiences to aggressive behavior of male students at State Vocational School 5 Padang. The phenomenon of aggressive behavior is often influenced by psychological and social factors, including narcissistic tendencies and social rejection, which can worsen interactions between students. The sample of this study consisted of 182 male students selected by purposive sampling. The method used was quantitative with a correlational approach, using a questionnaire instrument that measured narcissistic tendencies (NT), experiences of social rejection (ESR), and aggressive behavior (AB). Data analysis showed that narcissistic tendencies have a significant contribution to aggressive behavior, with a fairly high correlation coefficient (r = 0.374, p < 0.05). Meanwhile, social rejection also showed a significant contribution to aggressive behavior (r = 0.507, p < 0.05). A significant contribution between narcissistic tendencies and social rejection (r = 0.524, p<0.05). These findings indicate that students with high narcissistic tendencies and experiences of social rejection tend to be more prone to exhibit aggressive behavior. The importance of psychological and social interventions in the school environment to minimize aggressive behavior and improve students' social relationships. Holistic approach strategies and social support are expected to reduce the negative impact of narcissistic tendencies and experiences of social rejection, thus creating a more conducive learning environment.